Tipologi Pembaruan Hukum Keluarga Islam di Ghana - Mochammad Agus Rachmatulloh; Iva Nikmatul Khusna (UNIVERSITAS BONDOWOSO, 2021)
This article describes the development of Islamic family law in Ghana, from marriage, polygamy to divorce, as well as the typology in its renewal. Islamic family law has been regulated in Islamic law. However, in practice, the life of the nation and state always requires development and renewal, in line with the changing times, places, times, and conditions. Using historical methods, descriptive in nature, with inductive analysis, and arranged in the form of a narrative that is creative and in-depth. The formulation of the problem is: (1) How is the development of Islamic family law in Ghana? (2) What is the typology of Islamic family law reform in Ghana? The result is that the development of Islamic family law in Ghana was influenced by customary law and colonial law. The typology of reform combines intradoctrinal reform and extradoctrinal reform, which emphasizes rational and contextual considerations to create a modern and just society.